Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's find an algebraic expression for [tex]\(\cos(\arcsin(3x) + \arccos(x))\)[/tex] that does not involve trigonometric functions.
To solve this, we can use the following trigonometric identities:
1. [tex]\(\arcsin(y) + \arccos(y) = \frac{\pi}{2}\)[/tex] for any [tex]\(y\)[/tex] within the domain of both arctangent functions,
2. [tex]\(\cos(A + B) = \cos A \cos B - \sin A \sin B\)[/tex].
Given:
[tex]\[ A = \arcsin(3x) \][/tex]
[tex]\[ B = \arccos(x) \][/tex]
We need to find:
[tex]\[ \cos(\arcsin(3x) + \arccos(x)) \][/tex]
From the identity [tex]\(\cos(A + B) = \cos A \cos B - \sin A \sin B\)[/tex]:
[tex]\[ \cos(\arcsin(3x) + \arccos(x)) = \cos(\arcsin(3x)) \cos(\arccos(x)) - \sin(\arcsin(3x)) \sin(\arccos(x)) \][/tex]
Now, evaluate each trigonometric function:
1. [tex]\(\cos(\arcsin(3x))\)[/tex]:
[tex]\[ \sin(\arcsin(3x)) = 3x \][/tex]
We know that [tex]\(\sin^2 A + \cos^2 A = 1\)[/tex], so,
[tex]\[ \cos(\arcsin(3x)) = \sqrt{1 - \sin^2(\arcsin(3x))} = \sqrt{1 - (3x)^2} = \sqrt{1 - 9x^2} \][/tex]
2. [tex]\(\cos(\arccos(x)) = x\)[/tex] (by definition).
3. [tex]\(\sin(\arccos(x))\)[/tex]:
[tex]\[ \cos(\arccos(x)) = x \][/tex]
Similarly, [tex]\(\sin^2 B + \cos^2 B = 1\)[/tex], so,
[tex]\[ \sin(\arccos(x)) = \sqrt{1 - \cos^2(\arccos(x))} = \sqrt{1 - x^2} \][/tex]
Put these back into our main expression:
[tex]\[ \cos(\arcsin(3x)) \cos(\arccos(x)) - \sin(\arcsin(3x)) \sin(\arccos(x)) \][/tex]
[tex]\[ = (\sqrt{1 - 9x^2})(x) - (3x)(\sqrt{1 - x^2}) \][/tex]
[tex]\[ = x \sqrt{1 - 9x^2} - 3x \sqrt{1 - x^2} \][/tex]
Therefore, the algebraic expression for [tex]\(\cos(\arcsin(3x) + \arccos(x))\)[/tex] is:
[tex]\[ \boxed{x \sqrt{1 - 9x^2} - 3x \sqrt{1 - x^2} } \][/tex]
To solve this, we can use the following trigonometric identities:
1. [tex]\(\arcsin(y) + \arccos(y) = \frac{\pi}{2}\)[/tex] for any [tex]\(y\)[/tex] within the domain of both arctangent functions,
2. [tex]\(\cos(A + B) = \cos A \cos B - \sin A \sin B\)[/tex].
Given:
[tex]\[ A = \arcsin(3x) \][/tex]
[tex]\[ B = \arccos(x) \][/tex]
We need to find:
[tex]\[ \cos(\arcsin(3x) + \arccos(x)) \][/tex]
From the identity [tex]\(\cos(A + B) = \cos A \cos B - \sin A \sin B\)[/tex]:
[tex]\[ \cos(\arcsin(3x) + \arccos(x)) = \cos(\arcsin(3x)) \cos(\arccos(x)) - \sin(\arcsin(3x)) \sin(\arccos(x)) \][/tex]
Now, evaluate each trigonometric function:
1. [tex]\(\cos(\arcsin(3x))\)[/tex]:
[tex]\[ \sin(\arcsin(3x)) = 3x \][/tex]
We know that [tex]\(\sin^2 A + \cos^2 A = 1\)[/tex], so,
[tex]\[ \cos(\arcsin(3x)) = \sqrt{1 - \sin^2(\arcsin(3x))} = \sqrt{1 - (3x)^2} = \sqrt{1 - 9x^2} \][/tex]
2. [tex]\(\cos(\arccos(x)) = x\)[/tex] (by definition).
3. [tex]\(\sin(\arccos(x))\)[/tex]:
[tex]\[ \cos(\arccos(x)) = x \][/tex]
Similarly, [tex]\(\sin^2 B + \cos^2 B = 1\)[/tex], so,
[tex]\[ \sin(\arccos(x)) = \sqrt{1 - \cos^2(\arccos(x))} = \sqrt{1 - x^2} \][/tex]
Put these back into our main expression:
[tex]\[ \cos(\arcsin(3x)) \cos(\arccos(x)) - \sin(\arcsin(3x)) \sin(\arccos(x)) \][/tex]
[tex]\[ = (\sqrt{1 - 9x^2})(x) - (3x)(\sqrt{1 - x^2}) \][/tex]
[tex]\[ = x \sqrt{1 - 9x^2} - 3x \sqrt{1 - x^2} \][/tex]
Therefore, the algebraic expression for [tex]\(\cos(\arcsin(3x) + \arccos(x))\)[/tex] is:
[tex]\[ \boxed{x \sqrt{1 - 9x^2} - 3x \sqrt{1 - x^2} } \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.